Energy characteristics of mixed-flow pump under different tip clearances based on entropy production analysis. (15th May 2020) - Ji, Leilei; Li, Wei; Shi, Weidong; Chang, Hao; Yang, Zhenyu
Abstract: In order to investigate the effect of impeller tip clearance on the internal flow fields and the hydraulic losses in mixed-flow pump, the entropy production method with computational fluid dynamics (CFD) is employed to analyze the energy losses in a low specified number mixed-flow pump with guide vane. The results show that the size of tip clearance is closely related to the external characteristic performance of mixed-flow pump, and the effect of tip clearance on the flow fields of mixed-flow pump is obvious at design flow rate condition. When the tip clearance raises from 0.2 mm to 1.1 mm, the head drop loss coefficient increases 1.62 times in the impeller. As the tip clearance augments from 0.2 mm to the 1.1 mm, the total entropy production in impeller increases by 142%. Whereas, the total entropy production in guide vane descends by 21.8% slightly. It indicates that the increase of tip leakage flow (TLF) may increase the energy losses in impeller but the hydraulic losses in guide vane is suppressed to some extent as a result of an existence of TLF. Therefore, for the sake of improving the energy performance of mixed-flow pump, it is necessary to take the scale of blade tip clearance into account and consider optimizing the hydraulic design structure of guide vanes comprehensively to match the tip clearance. Highlights: Energy losses induced by tip leakage flow are analyzed by entropy production method. The effect of tip clearance size on head loss of pump is analyzed in detail. Entropy production in impeller is positively correlated with tip clearance. Entropy production in guide vane is negatively correlated with tip clearance. Tip clearance size and structure of guide vane are essential to optimize the pump.